Lethal and sub-lethal effects of bio-and chemical insecticides on the tomato leaf miner, Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) - Mohamed A. Kandil; Rania N. Abdel-kerim; Moataz A. M. Moustafa (Egyptian Journal of Biological Pest Control, 2020)
Abstract The tomato leaf miner, Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae), is a destructive pest affecting the tomato crop causing a loss of 60–100% of the tomato crop production. In the present study, the lethal and sub-lethal effects of Bacillus thuringiensis (Bt), spinosad, and emamectin benzoate as bio-insecticides comparing with 2 synthetic insecticides: chlorpyrifos and indoxacarb against T. absoluta under laboratory conditions were evaluated. Take in consideration, life tables and reproductive parameters of treated larvae with LC30 for each pesticide (bio- and chemical insecticides) by using leaf dipping technique were calculated. The results showed that Lepinox formulation of Bt was the most effective one against the early 2nd instar larvae with 0.01 × 10−2 mg/l (ppm), followed by spinosad with 0.07 × 10−2 ppm comparing to indoxacarb and chlorpyrifos (0.01 and 11.44 μg/ml, respectively). Sub-lethal effect of the Bt formulations significantly increased pupal mortality by 29.77, 33.30, and 26.94% for Lepinox, Dipel 2×, and Protecto, respectively. In addition to their efficiency, Bt formulations and emamectin benzoate increased larval developmental period and reduced adult emergency percentage to 70.28, 66.70, 73.06, and 75.55% for Lepinox, Dipel 2×, Protecto, and emamectin benzoate, respectively. All bio-insecticides including Bt, spinosad, and emamectin benzoate caused abnormalities in different life stages. The results suggest these bio-insecticides are promising alternatives to synthetic insecticides for T. absoluta management.